Monolithic laser scribed graphene scaffolds with atomic layer deposited platinum for the hydrogen evolution reaction. Issue 38 (21st September 2017) - Nayak, Pranati; Jiang, Qiu; Kurra, Narendra; Wang, Xianbin; Buttner, Ulrich; Alshareef, Husam N.
Abstract : Atomic layer deposition (ALD) of Pt over monolithic 3D porous, laser scribed graphene scaffolds forms an efficient electrocatalyst for the hydrogen evolution reaction. Abstract : Three-dimensional (3D) electrode architectures for conformal deposition and effective use of catalysts are an emerging area with significant interest in electrocatalytic applications. In this study, we report the fabrication of monolithic, self-standing, 3D graphitic carbon scaffolds with conformally deposited Pt by atomic layer deposition (ALD) as a hydrogen evolution reaction catalyst. Laser scribing is employed to transform polyimide into 3D porous graphitic carbon, which possesses good electronic conductivity and numerous edge plane sites. This laser scribed graphene (LSG) architecture makes it possible to fabricate a monolithic electrocatalyst support without any binders or conductive additives. The synergistic effect between the ALD of Pt and the 3D network of LSG provides an avenue for minimal yet effective usage of Pt leading to an enhanced HER activity. This strategy establishes a general approach for inexpensive and large scale HER device fabrication with minimum catalyst cost.